Butane hash oil and dabbing: insights into use, amateur production techniques, and potential harm mitigation - Al-Zouabi I; Stogner JM; Miller BL; Lane ES (Dove Medical Press, 2018)
Ihsan Al-Zouabi,1 John M Stogner,1 Bryan Lee Miller,2 Elizabeth S Lane1 1Department of Criminal Justice and Criminology, University of North Carolina at Charlotte, Charlotte, NC 28223-0001, USA; 2Department of Sociology, Anthropology and Criminal Justice, Clemson University, Clemson, SC 29631, USA Abstract: The use of marijuana concentrates has escalated in recent years with butane extracts appearing particularly popular. The administration of butane hash oil, colloquially referred to as “dabbing,” is distinct from traditional flower cannabis usage due to the THC content of samples and the presence of impurities such as unpurged butane. While this may confer heightened risk to the user, additional significant concerns are tied to fires and explosions. Using butane as a solvent in amateur “blasting” methods may result in a flammable vapor pooling in enclosed spaces and igniting when exposed to a spark. As research on butane extract users, amateur production techniques, health risks, and legality is in its infancy, we explored existing studies on the topic to create a review of substantiated knowledge related to THC extracted using butane. The resulting assessment centers on three areas: 1) dab users including both recreational users and medical marijuana patients; 2) butane extraction techniques including illicit amateur open methods and the safer closed-loop system employed in medicinal/recreational states; and 3) risks, both related to fires and legality. We follow the presentation of this material with a summary of the (mis)information reaching the public in print and online sources so that public educational campaigns can focus on dispelling the inaccuracies and false notions of safety that may be tied to amateur production. Keywords: butane hash oil, dabbing, dabs, marijuana, marijuana concentrates, blasting